MAPPING DESA TERKAIT INDEKS PEMBANGUNAN MANUSIA DI KECAMATAN KAIRATU DAN KAIRATU BARAT - Mohammad Ratmasa Serang (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2017)
This study aims to 1) Describe the actual conditions of education, health and welfare development of villagers in Kairatu and Kairatu Barat sub-districts of 2016. 2) Analyze the progress of human development that has been achieved by West Seram District in 2010-2015. 3) Calculating the size of HDI and its forming factors by village in Kecamatan Kairatu and Kairatu Barat 2016. 4) Analysis and mapping of villages related to HDI in Kecamatan Kairatu and Kairatu Barat 2016. Calculation method of Human Development Index (HDI) used in this research is New Method Year 2010. To improve the analysis result to determinant and performance of human development hence used qualitative descriptive analysis tool supported by table, graph / picture, area map, 4 quadrant matrix , ratios and percentages. During the period 2010-2015, achievements of human development performance in West Seram District showed an increasing trend year by year, with an average Human Development Index of 61.53% per year. This condition is supported / influenced by the economic performance of West Seram District, in the same period experienced an average growth of 6.03% per year. Nevertheless, the human development performance of West Seram District has not been satisfactory since it is still below the average of Maluku Province HDI. Local governments in Kairatu and Kairatu Barat sub-districts are still faced with a number of issues, namely 1) limited teachers and inadequate educational facilities. 2) limited health personnel and health infrastructure. Based on the results of HDI calculations at the village level in Kairatu and Kairatu Barat subdistricts, the first and second ranks are achieved by Kamal Village and Kairatu Village while Nuruwe and Lohiatala villages are ranked lowest. This condition is influenced by more advanced economic, health and education development in Kamal and Kairatu villages than other villages. In addition, low geographical and accessibility factors are the main constraints faced by villages with the lowest HDI ratings.